Indigenous Young People Transitioning from Out-of-Home Care (OOHC) in Victoria, Australia: The Perspectives of Workers in Indigenous-Specific and Non-Indigenous Non-Government Services - Philip Mendes; Bernadette Saunders; Susan Baidawi (International Indigenous Policy Journal, 2016)
Indigenous children and young people are overrepresented in the Australian out-of-home care (OOHC) system. To date, specific research has not been undertaken on workers' perspectives regarding the Indigenous-specific and non-Indigenous supports and services available to Indigenous young people exiting the system. This exploratory research involved focus group consultations with workers from seven child and family welfare agencies to examine the current support services available to Indigenous young people who are in or will be leaving out-of-home care in the State of Victoria. Findings suggest that Aboriginal Community Controlled Organisations (ACCOs) play a positive role in working with non-Indigenous agencies to assist Indigenous care leavers. Participants identified some key strategies to improve outcomes, such as facilitating stronger relationships between Indigenous and non-Indigenous services, and improving the resourcing of ACCOs.